Determining competence in performing obstetric combined spinal-epidural procedures in junior anesthesiology residents: results from a cumulative sum analysis. (November 2020) - Lew, E.; Allen, J.C.; Goy, R.W.L.; Ithnin, F.; Sng, B.L.
Highlights: Combined spinal-epidural (CSE) technique is a difficult anesthetic skill to learn. Cumulative sum (CUSUM) approach was used to define competence in CSE technique. 19 of 24 junior residents required at least 40 CSE attempts to achieve competence. CUSUM graphs highlighted performance trends of slow learners. Abstract: Background: The epidural anesthesia technique is a challenging skill to master. The Accreditation Council for Graduate Medical Education (ACGME) stipulates that anesthesiology residents must complete 40 epidural procedures by the end of junior residency. The rationale is unknown. The aim of this prospective study was to determine the minimum case experience required to demonstrate competence in performing obstetric combined spinal-epidural procedures among junior residents, using an objective statistical tool, the cumulative sum (CUSUM) analysis. Methods: Twenty-four residents, with no prior experience performing epidurals, sequentially recorded all obstetric combined spinal-epidural procedures as a 'success' or 'failure', based on study criteria. Individual CUSUM graphs were plotted, with acceptable and unacceptable failure rates set at 20% and 35%, respectively. The number of procedural attempts necessary to demonstrate competence was determined. Results: Twenty-four residents (mean (SD) age 29 (2) years) participated in the study. Median (IQR) number of procedures was 78 (66–85), with a median (IQR) success rate of 86% (82–89%). Nineteen of 24 residents required a median (IQR) of 40 (33–50) attempts to demonstrate competence. Five did not achieve procedural competence in the training period. The CUSUM graphs highlighted performance trends that required intervention. Conclusion: Competence was achieved by 19/24 residents after the ACGME-required case experience of 40 combined spinal-epidural procedures, based on a predefined acceptable failure rate of 20%. In our experience, CUSUM analysis is useful in monitoring technical performance over time and should be included as an adjunct assessment method for determining procedural competence.